The cardiovascular profile and pharmacology of vandetanib and pazopanib - Carter, Joanne (2017)
Angiogenesis, a process that enables the growth of blood vessels from a pre-existing vasculature and is common to all solid tumours greater than 1 mm3 in size (Gacche and Meshram, 2014). The angiogenic process is heavily promoted by vascular endothelial growth factor (VEGF). Compounds able to inhibit VEGF signalling have been shown to reduce cancer mass (Arjaans et al., 2016). However, VEGF receptor tyrosine kinase inhibitors (RTKIs), a class of anti-VEGF treatment, have been shown to cause cardio-toxicity, with hypertension being a commonly reported, and often severe, side effect (Eskens and Verweij, 2006; Widakowich et al., 2007; Abi Aad et al., 2015). Depending on the nature of the study, the incidence of hypertension in the VEGF RTKI patient population ranges from 23% to 90% (Hamberg et al., 2010; La Vine et al., 2010; Aparicio-Gallego et al., 2011; Bible et al., 2014). Due to the increasing incidence and seriousness of hypertension observed in oncology clinics, it is clear that there are important cardiovascular issues relating to the use of RTKIs, particularly those that target VEGF, that require further exploration. This body of work set out to determine the in vitro potencies of vandetanib, pazopanib, cediranib and sorafenib at VEGFR2, alongside the in vivo cardiovascular haemodynamic and vasoactive profile of vandetanib and pazopanib, two VEGF RTKIs shown to cause hypertension in approximately 32% (Wells et al., 2012) and 33%-40% of the patient population, respectively (Bible et al., 2014).